Estimating time-varying risk aversion from option prices and realized returns. Issue 1 (2nd January 2023) - Kosolapova, Maria; Hanke, Michael; Weissensteiner, Alex
Abstract : Risk aversion is estimated from risk-neutral densities and realized index returns